SRATEGI KOMUNIKASI DA’WAH FORUM DA’WAH PERBATASAN (FDP) DALAM MEMBINA MUALAF DI PULAU BANYAK - Ujang HabibiDan; Dan Jaini (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
Research purpose: The purpose of this research is to find out how the Communication Strategy of the Da'wah Border Da'wah Forum (FDP) in fostering the converts of Pulau Banyak community, Aceh Singkil Regency. In this study the authors used a qualitative method, and analyzed the data by using Anwar Arifin's theory. The results of the strategic research of the Border Da'wah Forum (FDP) include. 1). Knowing the audience by means of friendship, safari da'wah. 2). Compose messages by cadre da'i, and send da'i cadres to kepesanteren or kepondok. 3). Determining Methods by means of Persuasive Methods (Approaches), Educational Methods (Learning or Educating), Informative Methods (Providing Information), and Monitoring Methods (Evaluation).